(untitled) (European Journal of Pure and Applied Mathematics, 2024)
The present study investigates the relation between derivations and hyperideals on ordered hyperrings with no zero divisors. Also, we identify some results for the ordered hyperrings induced by the homomorphism of the ordered hyperrings by derivations. The present work explores some aspects of derivations in ordered hyperrings. Also, we establish some results in connection with homomorphisms and hyperideals. Furthermore, we describe prime hyperideals associated to a derivation d on an ordered hyperring T and derive several results about homomorphisms and derivations on ordered hyperrings.